2017
DOI: 10.2147/idr.s136777
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of colistin and fosfomycin resistance in carbapenem-resistant Enterobacteriaceae from a tertiary care hospital in Karachi

Abstract: IntroductionManagement of infections with carbapenem-resistant Enterobacteriaceae (CRE) is challenging. In recent times, agents such as colistin and fosfomycin have been used in combination with other antibiotics to treat such infections. In this study, we aim to seek frequency of colistin and fosfomycin resistance in CRE from Pakistan.MethodsThis study was conducted at clinical laboratories, Aga Khan University Hospital. In total, 251 CRE were included in the study. Colistin minimum inhibitory concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 22 publications
6
27
0
Order By: Relevance
“…Overall, 90.7 per cent of the isolates were susceptible to colistin. Süzük et al 24 from Turkey reported 96.8 per cent colistin susceptibility among CRE, while a study from Pakistan25 found 84.1 per cent colistin susceptibility among CRE.…”
Section: Discussionmentioning
confidence: 94%
“…Overall, 90.7 per cent of the isolates were susceptible to colistin. Süzük et al 24 from Turkey reported 96.8 per cent colistin susceptibility among CRE, while a study from Pakistan25 found 84.1 per cent colistin susceptibility among CRE.…”
Section: Discussionmentioning
confidence: 94%
“…In a study conducted in a tertiary hospital in Pakistan, the rates of resistance to colistin and fosfomycin among the strains of CRE were found to be 15.9% and 12.3%, respectively. In this study, the colistin susceptibility test was performed by the broth microdilution technique and the fosfomycin susceptibility test was performed by the disk diffusion method, using fosfomycin trometamol disks [23]. EUCAST does not suggest using fosfomycin trometamol disks for the strains of Enterobacteriaceae except for the urinary E. coli strains [9].…”
Section: Discussionmentioning
confidence: 99%
“…Colistin resistance was associated with higher resistance rates to quinolones, fosfomycin and tobramycin, but not carbapenem resistance. Carbapenem-resistant Enterobacteriaceae are known to have concurrent resistance to colistin, fosfomycin and quinolones [ 16 - 18 ], but resistance clusters without concomitant carbapenem resistance have not been described so far and its role and aetiology remains unclear. High rates of colistin resistance in human samples have mainly been reported in countries with high proportions of carbapenem-resistant Gram-negative bacteria and subsequent widespread use of colistin in healthcare settings.…”
Section: Discussionmentioning
confidence: 99%